A time‐course investigation of resistance to the carboxylic acid amide mandipropamid in field populations of Plasmopara viticola treated with anti‐resistance strategies. Issue 12 (22nd July 2018) - Toffolatti, Silvia L; Russo, Giuseppe; Campia, Paola; Bianco, Piero A; Borsa, Paolo; Coatti, Mauro; Torriani, Stefano FF; Sierotzki, Helge
Abstract: BACKGROUND: Despite anti‐resistance strategies being recommended to reduce selection pressure on insensitive strains, no information is available on fungal population dynamics following their application in real field conditions. In this study, the effects on Plasmopara viticola populations of two identical spray programs, differing only in including or not the carboxylic acid amide (CAA) mandipropamid in mixture and in alternation with an anti‐resistance partner, were compared in terms of downy mildew control efficacy and mandipropamid sensitivity in two commercial vineyards for four seasons. RESULTS: Both programs effectively and similarly protected grapevine from downy mildew, despite different starting sensitivity levels of the P. viticola populations. In the vineyard where resistant strains were initially present, the frequency of mutations associated with resistance (G1105S/V) fluctuated within seasons in both programs and a shift towards sensitivity occurred after 3 years of the mandipropamid‐free program. Where sensitivity was initially present, no changes occurred in the mandipropamid‐free program and resistant strains were selected in the mandipropamid program in high disease pressure conditions. CONCLUSION: The anti‐resistance strategy including mandipropamid in mixture showed a good field performance, but did not completely prevent an increase in the frequency of insensitive strains. This supports the need for appropriate planning to determine which mixtures should be used in the field. © 2018 Society of Chemical Industry Abstract : Fungicide resistance management is crucial in plant disease protection. The effectiveness of anti‐resistance strategies under real field conditions is evaluated considering the complex interaction among fungicide, pathogen, host and environment.